Effect of brain-derived neurotrophic factor on c-jun expression in the rd mouse retina - Chen, Rui; Yin, Xiao-Bei; Peng, Chun-Xia; Li, Gen-Lin (International journal of ophthalmology, 2012)
AIM:To determine the location of c-jun protein,dynamic changes in c-jun mRNA and protein expression,and ultrastructure characteristics in the rd mouse retina,following a single dose of brain-derived neurotrophic factor(BDNF) in a short period of time.· METHODS:A single intravitreal injection of BDNF at two dosages(25μg/L or 50μg/L) was given to the right eye of the rd mouse at age 2 and 3 weeks respectively.Two weeks after injection,the location of c-jun protein in the retina was observed by immunofluorescence detection,c-jun mRNA and protein expression in retinas were detected by quantitative real time polymerase chain reaction(RT-PCR) and western immunoblotting analysis,ultrastructure characteristics of retinas were detected by transmission electron microscope(TEM) observation.· RESULTS:c-jun protein was expressed in the inner nuclear layer(INL) of retina.BDNF at two dosages(25μg/L and 50μg/L) increased c-jun mRNA expression at PN-4 weeks respectively(P1 =0.019,P2=0.021).50μg/L BDNF increased c-jun protein expression at PN-4 weeks(P =0.000).The retinal ultrastructure was improved.· CONCLUSION:The effects of BDNF exerts on the c-jun expression in the retina are dose-dependent and time-dependent,which may mediate photoreceptor rescue indirectly in the pathological process of retinitis pigmentosa(RP)at early stage.